Gonadothropin-releasing hormone agonist as a treatment of choice for central precocious puberty (Faculty of Medicine Universitas Indonesia, 2010)
Precocious puberty is defi ned as pubertal development which occurs too early. The age limit in this term is based on the onset of puberty in normal population. Some points have to be taken into account, such as ethnicity, gender, nutritional conditions, and secular trends. In girls, precocious puberty is defi ned by breast development occured before 8 years old. In boys, precocious puberty is defi ned as gonadarche or pubarche before 9 years of age. The clinical course of precocious puberty varies widely, ranging from alternating, slowly progressive, and rapidly progressiveÂ Â Â form. The rapidly progressive forms of idiopathic central precocious puberty need to be treated because it may result in early epiphyseal closure and short fi nal height, and also pyschosocial problems in the affected children and the family. The aims of treatment are to arrest physical maturation, prevent early menarche, and also improve adult height combined with normal body proportions. Gonadotropin releasing hormone analogue is the treatment of choice for central precocious puberty. Gonadotropin releasing horomone analogue has suppressive effect on the pituitarygonadal axis, therefore it suppresses LH secretion. This leads to the return of estradiol and testosterone to prepubertal levels. Treatment using gonadotropin releasing horomone analogue is shown to reduce breast size, pubic hair, ovarian and uterine size in girls, and decrease testicular size in boys. Gonadotropin releasing hormone analogue is effective in halting progression of secondary sexual characteristics development, presenting menstrual cycle, slowing bone-age advancement, and also improving fi nal height. (Med J Indones 2010; 19:287-92)Keywords: gonadache, GRH analogue, pubarche , precocious puberty